2006
DOI: 10.1086/505043
|View full text |Cite
|
Sign up to set email alerts
|

Radio-loud Narrow-Line Type 1 Quasars

Abstract: We present the first systematic study of (non-radio-selected) radio-loud narrow-line Seyfert 1 (NLS1) galaxies. Cross-correlation of the `Catalogue of Quasars and Active Nuclei' with several radio and optical catalogues led to the identification of 11 radio-loud NLS1 candidates including 4 previously known ones. Most of the radio-loud NLS1s are compact, steep spectrum sources accreting close to, or above, the Eddington limit. The radio-loud NLS1s of our sample are remarkable in that they occupy a previously ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
495
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(517 citation statements)
references
References 142 publications
(220 reference statements)
22
495
0
Order By: Relevance
“…2). Most of the mildly radio-loud NLS1 galaxies of Komossa et al (2006a) are steep-spectrum sources, and do not show indications of beaming, while three sources are more similar to blazars. In terms of their optical emission-line properties and BH masses, the RLNLS1s are similar to the radio-quiet NLS1 (RQNLS1) population as a whole.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…2). Most of the mildly radio-loud NLS1 galaxies of Komossa et al (2006a) are steep-spectrum sources, and do not show indications of beaming, while three sources are more similar to blazars. In terms of their optical emission-line properties and BH masses, the RLNLS1s are similar to the radio-quiet NLS1 (RQNLS1) population as a whole.…”
Section: Introductionmentioning
confidence: 93%
“…Remillard et al 1986, Oshlack et al 2001, Zhou et al 2003 seemed to be exceptions, rather than the tip of an iceberg. The early surveys revealed only a handful of objects: 11 by Zhou & Wang (2002) and Komossa et al (2006a), and 16 by Whalen et al (2006). Williams et al (2002) analysed 150 NLS1s from the Sloan Digital Sky Survey (SDSS) Early Data Release, and only a dozen (8%) were detected at radio frequencies and only two (1.3%) are radio loud, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Both paradigms are also discussed for γ-NLS1(e.g., Abdo et al 2009c;Foschini et al 2015;Berton et al 2015), and it has been proposed that CSS and RL-NLS1 are linked (e.g., Komossa et al 2006;Doi et al 2012;Caccianiga et al 2014;Komossa et al 2015;Gu et al 2015). Recently, Caccianiga et al (2015) have found evidence of significant star formation activity in a sample of RL-NLS1s, favouring the scenario that RL-NLS1s are young AGNs.…”
Section: Parsec-scale Structure and Jet Orientationmentioning
confidence: 99%
“…However, the total number of known RL-NLS1s has increased in recent years. The first dedicated study and search of RL-NLS1s was performed by Komossa et al (2006), yielding a sample of 11 sources most of which were previously not known to be RL-NLS1s. Then, Yuan et al (2008) compiled a genuine sample of 23 RL-NLS1s with RL 1.4 GHz > 100, with black hole masses of 10 6 -10 8 M and Eddingtion ratios R Edd ≈ 1.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, these objects are often branded "winged" or "X-shaped" radio galaxies (Leahy & Williams 1984;Leahy & Parma 1992). A recent merger of two supermassive black holes (SMBHs), where the wings constitute the relic emission of the past radio jets, is one of several scenarios proposed to explain this peculiar radio morphology (e.g., Rottmann 2001;Merritt & Ekers 2002;Komossa 2006;Gergely & Biermann 2009;Hodges-Kluck et al 2010b;Mezcua et al 2011). Alternative models employ jet-axis reorientation (e.g., Dennett-Thorpe et al 2002), two unresolved active galactic nuclei (AGN; Lal & Rao 2007), backflow of material from the main lobes into the wings (e.g., Leahy & Williams 1984;Capetti et al 2002;Hodges-Kluck et al 2010a;Landt et al 2010;Hodges-Kluck & Reynolds 2011), or non-ballistic precession assuming a pre-merger state of the two black holes (BHs; Gong 2008;Gong et al 2011).…”
Section: Introductionmentioning
confidence: 99%